The United States opioid epidemic - Lyden, Jennifer; Binswanger, Ingrid A. (Seminars in perinatology, 2019)
The United States opioid epidemic is a nationwide public health crisis. Initially driven by increased consumption and availability of pharmaceutical opioids, an increasing number of opioid overdoses are now related to heroin and illicitly manufactured fentanyl and fentanyl analogs. Addressing this epidemic requires addressing the stigma associated with opioid use disorders and its treatment, improving access to efficacious treatment options, specifically methadone and buprenorphine, and reducing opioid overdose fatalities with distribution of the opioid antagonist and overdose reversal agent naloxone.